2013
DOI: 10.1016/j.applthermaleng.2013.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a compact thermal model for an aircraft compartment

Abstract: Highlights• Development of a reduced order model for the case of an aircraft crown compartment • A thermal fluid network is generated for its mixed convection regime • Regression analysis utilised to evaluate characteristic parameters • The thermal fluid network is simple but its accuracy is close to the detailed model *Highlights (for review) M A N U S C R I P T A C C E P T E D AbstractThe development of accurate structural/thermal numerical models of complex systems, such as aircraft fuselage barrels, is of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Heat flux measurements are important in many practical applications [1][2][3][4][5]. In micro-electric systems, increasing working efficiency and higher frequency of semiconductor devices require accurate measurement of the heat flux of heat dissipated by the devices [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Heat flux measurements are important in many practical applications [1][2][3][4][5]. In micro-electric systems, increasing working efficiency and higher frequency of semiconductor devices require accurate measurement of the heat flux of heat dissipated by the devices [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The current literature on thermal analysis in aircraft focuses mainly on passenger cabin studies [2,3]. Butler et al [4][5][6] published work for the aircraft crown area. With the advent of more electrical actuator technologies, several researchers focused on this particular aspect [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Butler et al [15] presented a methodology to optimise equipment placement in fuselage confined compartments and developed models to predict the convective heat transfer coefficients of equipment in a crown compartment. Stafford et al [10,16] and Geron et al [17] developed compact thermal-fluid models for the mixed convection regimes for equipment in an aircraft avionics bay and for an unpopulated fuselage compartment for inclusion in global thermal models. Gur et al [18] conducted a parametric design study to optimise the APU compartment and demonstrated its inclusion in a global model.…”
Section: Introductionmentioning
confidence: 99%